Premotor Symptoms as Predictors of Outcome in Parkinsons Disease: A Case-Control Study. - Yu-Hsuan Wu; Wei-Ju Lee; Yi-Huei Chen; Ming-Hong Chang; Ching-Heng Lin (PLoS ONE, 2016)
To evaluate the association between the premotor symptoms and the prognosis of PD.A total of 1213 patients who were diagnosed of PD from January 2001 to December 2008 were selected from the Taiwan's National Health Insurance Research Database. Patients were traced back to determine the presence of premotor symptoms, including rapid eye movement sleep behavior disorder (RBD), depression, and constipation. Cox's regression analysis was used to detect the risks between the occurrence of premotor symptoms and the outcome (including death, psychosis, accidental injury, dementia and aspiration pneumonia). In addition, the association between premotor symptoms and levodopa equivalent dosage (LED) was examined.Higher occurrence of death, dementia and aspiration pneumonia were identified in PD patients with premotor symptoms than without premotor symptoms (HR 1·69, 95% CI 1·34-2·14, p <0·001 for death; HR 1·63, 95% CI 1·20-2·22, p = 0·002 for dementia; HR 2·45, 95% CI 1·42-4·21, p = 0·001 for aspiration pneumonia). In a comorbidities-stratified analysis, PD patients with premotor symptoms showed significantly high risks of mortality and morbidity (dementia and aspiration pneumonia), especially in the absence of comorbidities. Independent predictors of mortality in PD were found to be higher age, male sex, constipation, RBD, RBD with constipation and depression, and diabetes. Furthermore, no significant differences of LED and subsequent accidental injury were noted between PD patient with or without premotor symptoms.Premotor symptoms seem to be not merely risk factors, but also prognostic factors of PD.